(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the world, interest in the Great Silk Road is in high demand. Culture, communication, economy, globalization, and tourism began with a global civilization network based on the Great Silk Road, and the development of major cultural centers continues to this day. The article is devoted to the interaction of cultures within the Silk Road and the exchange of cultures, which for many centuries were the only transcontinental route to Europe. With specific examples, the cultural transformation of the Great Silk Road as an urgent problem of cultural science. In the era of globalization, the Great Silk Road is a key factor in the exchange of cultures, the formation and development of different cultures. Cultural transformations and civilization prosperity on the Great Silk Road are very important for Kazakhstan. Each of the cultures involved in the cultural heritage of the Great Silk Road not only seeks to develop what they have, but also develops through self-understanding and mutual understanding through a creative synthesis of each other’s well-being and potential. Key words. The Great Silk Road, civilization, cultural tourism, globalization, intercultural communication, East and West, nomadic and intercultural interaction.